International Islamic Financial Institutions: Activities and Prospects for Cooperation with Uzbekistan - Djumanov, S. A.; qizi, Khamrokhujaeva Sitorabonu Temur (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In recent years, Uzbekistan has actively supported the development of Islamic finance on its territory. An important role in this process is played by international Islamic financial institutions that are part of the Islamic Development Bank group, as well as they conduct their activities autonomously. This article examines the prerequisites, goals and objectives of the IDB in Central Asia, as well as the measures taken by the government of the country to achieve bilateral cooperation with international organizations in the field of Islamic finance. Special attention is paid to the activities carried out by commercial banks aimed at expanding Islamic banking in the country.